2003
DOI: 10.1097/00003246-200301001-00003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intensive care unit (ICU) drug use on hospital costs: A descriptive analysis, with recommendations for optimizing ICU pharmacotherapy

Abstract: ICU drug therapies have a significant impact on hospital costs, and effective clinical informatics services and multidisciplinary collaboration programs are necessary to optimize ICU pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 32 publications
1
50
0
2
Order By: Relevance
“…Therefore, a large number of drugs are employed to save these patients and that make them susceptible to medication errors and adverse drug reactions [3]. According to the comparison held by Weber et al, 38% of the total drug costs are accounted for the ICU and these costs have increased at greater rate against non-ICU drug costs [4]. Furthermore, the cost of hospitalization and drug treatment in the ICU are also high [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a large number of drugs are employed to save these patients and that make them susceptible to medication errors and adverse drug reactions [3]. According to the comparison held by Weber et al, 38% of the total drug costs are accounted for the ICU and these costs have increased at greater rate against non-ICU drug costs [4]. Furthermore, the cost of hospitalization and drug treatment in the ICU are also high [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some developed countries reported that drug expenditure per patient per day in CCU ranging from $208 to $312 which was higher as compared to our study. 13,14 Average cost of antimicrobials in Group A patients was `4054 ± 2014 ($73 ± 36) which was significantly (p<0.05) higher as compared to Group B patients. It may be due to average number of antimicrobials as well as costliest antimicrobials were prescribed higher in Group A patients.…”
Section: Analysis Of Cost Of Group Of Drugs Per Patientmentioning
confidence: 89%
“…Bizim çalışmamızda da her iki YBÜ'de oluşan maliyetlerin SGK tarafından yapılan ödeme- Yapılan bir çalışmada YBÜ'de hasta günü başına ilaç maliyeti yıllık %12'lik artış göstermiştir. YBÜ dışındaki servislerde ise gün başına ilaç maliyeti yıllık %6'lık artış göstermiştir (15). Bizim çalışmamızda da ilaç maliyetlerinin önemli gider kalemlerinden biri olduğu ve iç hastalıkları YBÜ'de ilaç maliyetinin daha fazla olduğu gösterilmiştir.…”
Section: Yöntemlerunclassified